The Determinants of Bank Profitability in China under Lending Restriction and Supervision - Du, Lijin (2016)
This paper examined the impact of liquidity under lending restriction and supervision on profitability determinants for the profits growth of commercial banks in China, using a balanced panel data of 34 commercial banks during the period of 2009-2014. In our model, we choose Return on Assets (ROA) as the dependent variable and divide the determinants of bank profitability into internal and external factors, including liquidity ratios as a controlling independent variable. As we find that liquidity indicator is the endogenous variable of bank profitability, we use General Moment Movement (GMM) estimator to eliminate the effect of biased endogeneity and then measure significant factors contributed to promoting Chinese bank’s performance.